Insomnia Symptoms Following Treatment for Comorbid Panic Disorder With Agoraphobia and Generalized Anxiety Disorder. Issue 4 (April 2016) - Cousineau, Héloïse; Marchand, André; Bouchard, Stéphane; Bélanger, Claude; Gosselin, Patrick; Langlois, Frédéric; Labrecque, Joane; Dugas, Michel J.; Belleville, Geneviève
Abstract : Abstract: Patients with panic disorder with agoraphobia (PDA) or generalized anxiety disorder (GAD) frequently also suffer from insomnia. However, the impact of cognitive-behavioral therapy (CBT) for anxiety disorders on insomnia has been understudied. Furthermore, comorbidity between anxiety disorders is common. Our main objective was to assess the impact of CBT for PDA or GAD on insomnia. In a quasi-experimental design, 86 participants with PDA and GAD received conventional CBT for their primary disorder or combined CBT for both disorders. Overall, CBTs had a significant impact on reducing insomnia symptoms (η 2 = 0.58). However, among people with insomnia at pretest (67%), 33% still had an insomnia diagnosis, and the majority (63%) had clinically significant residual insomnia following treatment. In conclusion, the CBTs had a positive effect on the reduction of insomnia, but a significant proportion of participants still had insomnia problems following treatment. Clinicians should address insomnia during CBT for PDA and GAD.